Neonatal Coronavirus 2019 Infection in a tertiary setup of India: A case series - Saha, Jinia; Das, Tapas; Nayek, Kaustav (Asian Journal of Medical Sciences, 2021)
Covid-19 disease caused by SARS-COV-2 has been a pandemic throughout the world including India. It affects all age groups including children. The disease is much milder among children compared to adults. In neonates, the disease is often mild and has good prognosis. It is still doubtful whether there is vertical transmission to the neonates from infected mothers. Also, it is not proved whether the disease can be transmitted through breast milk. Here we present case reports of three neonates, two of which were born to COVID-19 positive mothers. Rest one got infected at 25 days of life. None of the two infants born to COVID-19 positive were positive at the time of birth. Our observation is similar to the previous studies that COVID-19 has not yet been proved to transmit vertically. One of them contracted the disease on day 7 of life from the mother in spite of strict precautions. It could not be proved whether it was transmitted from breast milk or faulty practice. One of the infants presented with late onset sepsis. All of the infants recovered well and was thriving well on follow up.